“Las TIC en el Aprendizaje de la Matemática” - Martínez Amaguaña, Wilson Alexander (2023)
In the digital era in which we are living encompasses many aspects of life and one of them is education, which is why it must go hand in hand with the technological advances that currently exist, the implementation of ICT in the classroom is a transcendental element that will allow the improvement of the teaching-learning process. In this sense, the research project called "ICT in the learning of mathematics" seeks to involve both students and teachers in the world of technology, because, through it, multiple educational benefits can be found. Therefore, the objective to be achieved is to apply the technological tool Educaplay to strengthen the learning process of mathematics in fourth grade students of EGB of the Unidad Educativa 14 de Julio JAE, Latacunga canton, province of Cotopaxi in the school year 2022-2023. This whole research process was developed through an interpretative approach, since it allows a deep analysis of the variables found, also the type of research used was qualitative because the characteristics of the project led to reflect subject to subjectivity of the researchers, on the other hand, the method used was inductive, which allows to find possible general relationships that support it from particular results; In this same line, the type of research gives way to the fact that the data collection technique is observation with its respective instrument, the observation guide, which orients to obtain more information from the informants. The results showed that the practical class achieved to get attention and interest due to the class was carried out in other context to break monotony and traditionalism. Besides was funny and functional as teachers as students, it is an innovating way to develop or improvise the teaching learning process.